2006
DOI: 10.1002/anie.200601925
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of the “Dialuminyne” Na2[Ar′AlAlAr′] and Na2[(Ar′′Al)3]: AlAl Bonding in Al2Na2 and Al3Na2 Clusters

Abstract: An alkyne analogue with Al: The first “dialuminyne” of formula Na2[Ar′AlAlAr′] (see picture; Ar′=C6H3‐2,6‐(C6H3‐2,6‐iPr2)2) was synthesized and characterized by X‐ray crystallography. The structure contains a planar trans‐bent C–Al–Al–C array with an AlAl bond length of 2.428(1) Å and a bending angle of 131.71(7)° at Al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
1
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 52 publications
8
120
1
9
Order By: Relevance
“…Similar alkali metal-π interactions are known in organometallic polymers prepared in arene solvents [18] as well as sodium-containing 'dialuminyne' species. [5] The [Al 4 (PPh 2 ) 7 PPh] -units are chiral and form homochiral chains that propagate along the 2 1 screw axis of the crystal lattice. Chains of alternating chirality pack in layers separated by the layers of solvate molecules ( Figure S2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar alkali metal-π interactions are known in organometallic polymers prepared in arene solvents [18] as well as sodium-containing 'dialuminyne' species. [5] The [Al 4 (PPh 2 ) 7 PPh] -units are chiral and form homochiral chains that propagate along the 2 1 screw axis of the crystal lattice. Chains of alternating chirality pack in layers separated by the layers of solvate molecules ( Figure S2b).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] Solutions of Al I halides have proven to be excellent precursors to low oxidation state Al I complexes, [7] such as Al 4 Cp* 4 , [8] but can also undergo redox (disproportionation) reactions to give new classes of clusters and compounds containing Al oxidation states from 0.27 to 3.0. [1,7] The most famous of these are the Al metalloid clusters that can be isolated during the disproportionation process: 3Al 1+ Ǟ Al 3+ + 2 Al 0 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the decamethylmetallocenium cations were excellent donors, leading to the formation of unprecedented donor-acceptor bonds. [25,26] All of these studies showed that the metal can interact with the Cp * ring by η 1 , η 2 , η 3 , and η 5 50 coordination via π-bonds. [22][23][24][25][26] Although low-valence aluminum compounds such as AlH, AlX (X=F, Cl, Br, I), and Al 2 O are well known, they are stable only at high temperatures and low pressures.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Examples for isolable neutral heavier group 13 dimetallenes with the formula of R-M = M-R (M: Al, Ga, In, Tl) remain scarce for the homologues of gallium, [4] indium, [5] and thallium, [6] and have been unknown for aluminum so far. [7][8][9] In 2003, Power et al reported the attempted synthesis of the 1,2-diaryldialumene A (Scheme 1). [10] Isolation of the compound B is likely interpreted in terms of the generation of A by the reduction of ArAlI 2 and subsequent trapping with toluene.…”
mentioning
confidence: 99%